High‐quality care improves outcome in recumbent dairy cattle. Issue 6 (June 2016) - Poulton, PJ; Vizard, AL; Anderson, GA; Pyman, MF
Abstract : Objective: To investigate the influence of the quality of care on outcome and occurrence of secondary damage in recumbent dairy cows. Methods: Recumbent dairy cows were monitored during their recumbency under field conditions in South Gippsland, Victoria, Australia. The cause of the original recumbency of 218 downer cows was determined and any secondary damage, day 7 status, final outcome and the nursing conditions of the cows were recorded. A four‐tiered grading system describing nursing quality was developed to allow analysis of its influence on outcome and on the occurrence of secondary damage. Results: Day 7 outcome, final outcome and occurrence of important secondary damage were very strongly associated with the level of overall care provided to the recumbent cows. There was a decrease in the percentage of cows recovering by day 7 from 33% to 0%, a decrease from 45% to 0% of cows eventually recovering and an increase from 68% to 100% of cows with clinically important secondary damage as overall care decreased. Conclusion: Management of recumbent cattle is potentially a significant animal welfare issue for the dairy industry and their care is a very important but often under‐appreciated aspect of their management. Recovery is positively influenced by high‐quality care by improving the chances of recovery from the initial cause of recumbency and by reducing the occurrence of secondary damage. Recumbent cows must either be nursed at a high level of care or euthanased promptly.